2020
DOI: 10.3390/ijerph17218163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Feasibility of a Two-Week Course of Aquatic Therapy and Thalassotherapy in a Mild Post-Stroke Population

Abstract: Strokes are a leading cause of disability in developed countries. Patients with disabilities need rehabilitation to improve their physical functioning, mental status, and quality of life. Currently, no high-quality evidence can be found attesting the benefits of any of the interventions that are nowadays used. Water-based exercise may improve the physical conditions and quality of life of people in the post-stroke phase. The objective of this study is to test whether aquatic therapy in an enriched environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
1
1
1
Order By: Relevance
“…When combined with land-based therapy, aquatic therapy proved successful in enhancing cadence. The study's findings conflict with those of Morer et al (2020), who reported that there was no significant improvement in gait speed over a short distance, the ten-meter walk test, but that there was a significant improvement for a longer running time, the six-minute walk test, following two weeks of aquatic therapy. Each session included two components: thalassotherapy (ten minutes in the water bath and an hour of outdoor activity for exposure to the environment), and aquatic therapy (Sayfullaevich, et al, 2021).…”
Section: Discussioncontrasting
confidence: 96%
“…When combined with land-based therapy, aquatic therapy proved successful in enhancing cadence. The study's findings conflict with those of Morer et al (2020), who reported that there was no significant improvement in gait speed over a short distance, the ten-meter walk test, but that there was a significant improvement for a longer running time, the six-minute walk test, following two weeks of aquatic therapy. Each session included two components: thalassotherapy (ten minutes in the water bath and an hour of outdoor activity for exposure to the environment), and aquatic therapy (Sayfullaevich, et al, 2021).…”
Section: Discussioncontrasting
confidence: 96%
“…Balneotherapy facilities could provide to post-COVID-19 subjects neuromotor rehabilitation with in-water muscle strength and balance exercises and walking recovery (Musumeci et al 2018 ; Masiero et al 2019 ; Morer et al 2020 ) enhancing cardiac (Pagourelias et al 2011 ; Sato et al 2009 ; Yuan et al 2019 ; Persiyanova-Dubrova et al 2019 ; Karaarslan et al 2018 ) or pulmonary performance (Baldi et al 2015 ; Khaltaev et al 2020 ). Moreover, balneotherapy may contribute to the management of comorbidities frequently existing in patients recovered from COVID-19: such as obesity and additional neurological and/or musculoskeletal conditions (Bender et al 2014 ; Fioravanti et al 2015b ; Masiero et al 2018 ; Özkuk and Dilekçi 2019 ; Munteanu et al 2019 ; Özkuk and Uysal 2019 ; Koç et al 2021 ; Eröksüz et al 2020 ; Cantista and Maraver 2020 ; Takinacı et al 2019 ; Dilekçi et al 2019 , 2020 ; Kamioka et al 2020b ; Tenti et al 2020 ; Özkuk and Ateş 2020 ; Yücesoy et al 2021 ; Karaarslan et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2017). Terapi akuatik dan thalassoterapi intensif selama selama dua minggu juga bermanfaat dalam jangka pendek dengan mengurangi rasa sakit dan meningkatkan status fungsional dan kesejahteraan pasien pasca stroke secara keseluruhan (Morer et al, 2020).…”
Section: Terapi Cahayaunclassified